Essential fashion illustration : digital - Streeter, Loreto Binvignat (Rockport Publishing, 2010)
Essential Digital Fashion Illustration' is a complete, in-depth tutorial that guides readers step-by-step through the digital techniques typically employed in fashion design and illustration.- Resumé vydavatel
Keywords: módní kresba; grafický design; vizuální komunikace; Adobe Illustrator (software); Adobe Photoshop (software); fashion drawing; computer graphics; visual communication; elektronické knihy; příručky; electronic books; handbooks and manuals